Green IoT based plant growth monitoring system - Kamruzzaman, Syed Md.; Hoque, Md. Aminul; Ahmed, Azmir (Brac University, 2019)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Electrical and Electronic Engineering, 2018.